Life Skill Berinovasi Dalam Usaha Kreatif dan Berguna Untuk Masyarakat Melalui Implementasi Enterpreneurship - Nurhasanah, Dinna; Nelaz, Yolanda Safitri; Afriayini, Neni; Pratiwi, Lidya Prajawati; Piliang, Arfah; S, Salman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The purpose of this study is to find out how to build a creative entrepreneurial spirit and how to apply the tradition of entrepreneurship in the midst of increasing economic pressures and increasingly narrow job opportunities. This study aims to find out how entrepreneurship can be an effective way to revive economic development from a small scale to becoming a driver of large-scale economic development. This study uses the literature review method, namely a literature review that aims to solve problems. The results of the literature review show that family, education, and government are three traditions that are able to build the application of entrepreneurship in society. Thus, this study can contribute to the development of entrepreneurship and community economic development. Here are some important points from this study: 1. Building a creative entrepreneurial spirit: This study aims to find out how to build a creative entrepreneurial spirit in society. 2. Application of the tradition of entrepreneurship: This study aims to find out how the application of the tradition of entrepreneurship can help drive economic development.  3. Family, education, and government: The results of the study show that family, education, and government are three traditions that are able to build the application of entrepreneurship in society.